POTENTIAL OF EUGENIA UNIFLORA AS A NATURAL ANTIBACTERIAL AGENT: A SYSTEMATIC REVIEW - Putu Ririn Andreani; I Kadek Suardiana; Ni Luh Putu Kris Monika Yanti (Journal Pharmaceutical Science and Application, 2026)
Background: Eugenia uniflora (family Myrtaceae), a medicinal plant traditionally used for the treatment of infectious and inflammatory diseases, has attracted increasing interest due to its potential antibacterial properties. Objectives: This systematic review aimed to comprehensively evaluate and synthesize published evidence on the antibacterial activity of E. uniflora. Methods: A systematic review was conducted following the PRISMA guidelines by searching Scopus, ScienceDirect, PubMed, and Google Scholar for English-language original studies published between 2015 and 2025 that evaluated the antibacterial activity of Eugenia uniflora. Of the 296 records identified, nine studies met the eligibility criteria and were included in the final analysis. Results: Nine included studies consistently demonstrated antibacterial activity of E. uniflora against both Gram-positive and Gram-negative bacteria. Gram-positive bacteria were generally more susceptible than Gram-negative bacteria, while antibacterial activity varied according to the plant part, extraction method, solvent, and extract concentration. Several studies also reported low minimum inhibitory concentration (MIC) values and broad-spectrum antibacterial activity, supporting the therapeutic potential of E. uniflora. Conclusions: The findings of this systematic review support the antibacterial potential of E. uniflora; however, further standardized and well-designed studies are necessary to confirm its efficacy and support its use and development as a natural antibacterial agent.  Keywords:  Eugenia uniflora; Antibacterial activity; Medicinal plants; Systematic review